Diretrizes para uso da comunicação social como forma de conscientização popular sobre a importância da biodiversidade em Angola - Nganda, Nsenga Yolanda Kiafuka (2013)
Angola’s biodiversity is one of the greatest on the African continent. It is, however, experiencing problems of keeping and meeting the needs of its population. After having experienced more than thirty years of war, the country wishes to develop economically and socially while attending and providing for its people fairly without compromising the natural resources available for future generations. This paper aims to discuss issues of economic growth and social development associated with the prospect of conserving biodiversity in Angola. At the end are guidelines for using media as a means for public awareness concerning the importance of biodiversity conservation in Angola. In order to carry out this study, a bibliographic study and examination of research papers from Angolan governmental institutions along with informal interviews with technical ministries related to this topic were made. The results demonstrate that the actions performed by the population affect the sustainability of the resources available in the country leading to a reduction in biodiversity, requiring immediate and effective responses in order to change the current situation. There needs to be a collaboration of public and private institutions in this regard. The proposed guidelines refer to the creation of a Communication Network for the Conservation of Biodiversity of Angola - RECOBIO, involving the integration of three ministries, the Ministry of Urbanism and Environment of Angola, the Ministry of Education and Ministry of Social Communication, which would form a multidisciplinary and multisectoral team in which the importance of conserving and preserving the environment through different media should be addressed in order to raise awareness of the entire population, business and government of the country.